Pelatihan Design Grafis Online Menggunakan Aplikasi Canva Bagi Remaja Majelis Ta’lim Hidayatul Mubtadiin - Aulianita, Rizki; Yunita, Norma; Rakhmah, Syifa Nur; Nisa , Khoirun (LPPM UMRI, 2023)
Training or workshop is one way to hone one's interests and deepen one's talents. In this community service that has been carried out for the odd 2022-2023 period, we as Nusa Mandiri University lecturers carry out community service activities by carrying out Canva training. The Canva application that we use as a learning media tool for the youth of the Hidayatul Mubtadiin ta'lim assembly. This Canva training was attended by teenagers and the parents of the board of directors of the Hidayatul Mubtadiin ta'lim assembly in Tangerang City. This training aims to improve the ability of millennial youth in mastering Graphic Design, which is useful for increasing youth creativity in entrepreneurship such as making billboards, making banner posters. Logo, template for branding on social media. The method used is Waterfall, with a focus on building products or works using the Canva application. We obtained the results of the training through the distribution of questionnaires. The results of the training showed that 98% of the youth partners of the ta'lim assembly were satisfied with the activity. The assessment variables are mastery of the material, discipline, and satisfaction, each of which gets a score of Very Satisfactory Grade A. Keywords: servant, Canva